Eksplorasi Penggunaan Ketum dalam Kalangan Belia di Negeri Kedah (Jurnal Pembangunan Sosial, 2017)
Ketum or its scientific name Mitragyna Speciosa has been used in traditional medical practice to treat certain diseases. Recently, ketum has been used widely to replace the synthetic drugs. The mixture of the leaves and other substances such as paracetamol, mosquito coil powder, and soda water are boiled to produce ketum juice. The juice has similar impact as synthetic or traditional drugs on human body that contributes to addiction. This problem is particularly prevalent in Northern States of Peninsular Malaysia. Therefore, this study aims to explore the ketum consumption among youths in the state of Kedah. The perception of seven subjects interviewed have shown that the ketum juice contributes to good health and at the same time serves as an alternative to drugs. The subjects were aware that the excessive use of ketum juice can lead to injury and fatality. These findings are important to help the professionals such as social worker and counselor in understanding the ketum consumption practice. The input will help them to come up with an appropriate interventions and programs to address the issue especially among youth.